Design of Intelligent Garbage Bin Control System Based on PLC Technology - Pan, Songzhe; Tang, Jianhao; Chen, Peike; Xia, Longlong (International Journal of Computer Science and Information Technology, 2024)
In recent years, driven by global environmental policies and technological innovation, smart trash cans have become an important innovative tool for urban environmental health management, as a product of the deep integration of Internet of Things technology, sensor technology, and automatic control technology. This type of garbage bin not only achieves intelligent operations that traditional containers cannot match, such as automatic sensing of opening and closing, precise guidance for garbage classification and disposal, but also monitors the garbage loading in real time through built-in sensors, accurately determines whether the garbage bin is fully loaded, and timely notifies for cleaning, avoiding environmental pollution problems caused by overflow. In addition, some high-end smart trash cans are even equipped with automatic compression function, significantly improving the garbage carrying capacity per unit volume, reducing the number of cleaning times, and saving resources.